Presence of anatomical variations of the circle of Willis in patients undergoing surgical treatment for ruptured intracranial aneurysms - Stojanović Nebojša; Stefanović Ivan; Ranđelović Saša; Mitić Rade; Bošnjaković Petar; Stojanov Dragan (Vojnosanitetski Pregled, 2009)
Background/Aim. The presence of aneurysmal changes on the brain blood vessels has been subject to numerous research. This study investigated the relation between ruptured aneurysms and anatomical configuration of the Circle of Willis, with the purpose to obtain an insight into their mutual connection. Methods. The analysis included 114 patients suffering from ruptured intracranial aneurysms. Preoperative cerebral angiography was performed and compared with the intraoperative findings in order to attain a precise insight into morphological changes occurring on the circle of Willis. Results. The prevalence of asymmetrical Willis in the whole group of patients was 64%. Within the group of patients suffering from multiple aneurysms, the presence of asymmetrical Willis' circle was 75.7%. The highest incidence of the asymmetrical Circle of Willis was found among patients with aneurysmal rupture detected at the anterior comunicative artery (ACoA) site (72.7% among cases with solitary and 100% among those with multiple aneurysms). Morphological changes on the A1 segment of ACoA were observed in 50 (44%) cases, with higher incidence found on the right side (60%). When comparing location of ruptured aneurysms between genders, a statistically significant prevalence of the ruptured aneurisms on ACoA was present in men, whereas women showed higher incidence of ruptured aneurysms on interior cartid artery (ICA) site (p < 0.01). The linkage between aneurysms with hypoplasia of the A1 segment of ACA and decreasing of the angle at which segments A1 and A2 join suggests the relationship between their onset, corresponding configuration type of Willis and subsequent hemodynamic changes. Conclusion. High incidence of asymmetry of Willis circle in the group of patients with ruptured aneurysms imply association of asymmetrical configuration and disorder in haemodynamic relations with forming and rupture of intracranial aneurysms.